Implementasi Sustainable Edible Landscaping Untuk Mitigasi Urban Heat Island. Pilot Project: Pemukiman Kebun Bibit, Kelurahan Hajimena, Lampung Selatan - Khotimah, Siti Nurul; Istiyanti, Lita; Alami, Fikri; Martinus; Lisa, Diana; Fadillah, Ihsanuddin; Amelia, Ananda; Ristanti, Dina Endang; Wulandari, Qanita (Nemui Nyimah, 2024)
Urban Heat Island (UHI) is a phenomenon that causes the surface temperature of a city to be higher than the surrounding area due to changes in land cover. To overcome the negative impacts of UHI, especially in the Kebun Bibit Settlement, Hajimena Village, South Lampung, a Community Service program was implemented with the implementation of Sustainable Edible Landscape (SEL). This program consists of two main parts: education about UHI and SEL and implementation of SEL. Education is carried out using interactive media to increase public understanding of UHI and the benefits of SEL in mitigating it. Furthermore, the implementation of SEL involves land preparation, preparation of planting media, sowing seeds, and planting vegetables with the aim of mitigating UHI and increasing food security and the local economy. Evaluation was carried out with pre-tests and post-tests, showing a significant increase in public understanding of UHI and SEL. This activity is expected to improve environmental conditions and improve community welfare.